2019
DOI: 10.1186/s12889-019-7573-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a statewide public health intervention to reduce cardiovascular disease risk

Abstract: Background The cost-effectiveness of community health worker (CHW)-based cardiovascular disease (CVD) risk-reduction interventions is not well established. Colorado Heart Healthy Solutions is a CHW-based intervention designed to reduce modifiable CVD risk factors. This program has previously demonstrated success, but the cost-effectiveness is unknown. CHW-based interventions are potentially attractive complements to healthcare delivery because laypersons implement the intervention at a lower cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
(22 reference statements)
0
13
0
1
Order By: Relevance
“…So the research requires a number of data that are actual and contextual in nature. In addition, the qualitative approach has a high adaptability to changes that occur, and allows the author to constantly adapt to the changing conditions and situations encountered in this research [9]. The research location chosen by the author is in the Service Technical Implementation Unit of the Talise Health Center with the consideration that the Talise Health Center is the health center that provides the most direct services to the community and is one of the Complaints Unit Pilot Projects in Palu City.…”
Section: Methodsmentioning
confidence: 99%
“…So the research requires a number of data that are actual and contextual in nature. In addition, the qualitative approach has a high adaptability to changes that occur, and allows the author to constantly adapt to the changing conditions and situations encountered in this research [9]. The research location chosen by the author is in the Service Technical Implementation Unit of the Talise Health Center with the consideration that the Talise Health Center is the health center that provides the most direct services to the community and is one of the Complaints Unit Pilot Projects in Palu City.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the evaluation of the effectiveness of the environmental health services in the primary health care on the patients with pulmonary TB using model approach of system resources, namely the rate of the variable input, process and output by considering the needs of the patient against the health services program for the environment (11). Input variables included policy, human resources, infrastructure and budget.…”
Section: Methodsmentioning
confidence: 99%
“…One study evaluating the cost-effectiveness of cardiovascular screening performed by Smith et al out of Colorado demonstrated a screening tool in combination with community health workers reaching out to individuals to implement interventions resulted in a 0.8% reduction in Framingham risk score in the general population and a 2.0% reduction in an at-risk population. In their cost analyses, they demonstrated not just an increase in quality-adjusted life-years (QALYs) but, more importantly, a significant savings in healthcare costs in both the general population as well as an at-risk population [ 19 ]. Given the large proportion of pregnancy-related mortality attributed to cardiovascular disease, these data suggest that an implementation of universal screening may be beneficial to overall healthcare costs in addition to improvement of overall maternal outcomes; however, a secondary analysis of healthcare-related costs would be indicated after implementation of our algorithm.…”
Section: Universal Cardiovascular Risk Assessment In Pregnancy and Po...mentioning
confidence: 99%